Frontal Horn of Lateral Ventricle of Brain and Its Relation with Age, Gender and Side: Morphometric Study by Computed Tomography among Bangladeshi Population - Basak, Dipannita; Yesmin, Nadia; Tasmia, Kimty; Chowdhury, Kakoli; Zahur, Tamanna; Roy, Sanchita; Sumaiya, Sarah Fatima (IAHS Medical Journal, 2024)
Background: Knowledge of the baseline reference value of frontal horn size is necessary for the initial and precise analysis of ventriculomegaly. The purpose of this study was to determine the size of frontal horn of lateral ventricle and its relation with age, gender and side among adult Bangladeshi population of Chattogram district. Materials and methods: This cross-sectional analytical study was conducted during the period from July 2022 to June 2023 in the Department of Anatomy, Chittagong Medical College, Chattogram, upon 150 respondents of 20-60 years who had normal Computed Tomography (CT) scans as reported by an expert radiologist. For statistical analysis, Mann-Whitney U test, Wilcoxon signed rank test and ANOVA test were done. p-value was considered significant if it was <0.05 at 95% level of confidence. Results: The mean right and left frontal horn length was 25.50 (±3.95) mm and 25.28 (±4.04) mm respectively. The length of the frontal horn of both right and left sided lateral ventricle were significantly higher in male than that of female (p<0.01). Spearman's correlation coefficient indicated positive linear correlation of length of frontal horn (Right and left side) with age, insignificant in right side (p=0.061) but significant in left side (p=0.046). Conclusion: Morphometric analysis of the frontal horn of the lateral ventricles among the Bangladeshi population produced a number of significant results that may help with the early diagnosis and treatment of neurological diseases that are particular to gender and age. These findings can be validated and expanded upon in future research using bigger sample sizes and cutting-edge imaging methods. IAHS Medical Journal Vol 7(1), June 2024; 54-59